The perception of Iraqi people on the Malaysian Islamic Banking System - A Abdurazzak, Ehab (2013)
The purpose· of this research is to find the challenges and the problems that might face the Iraq banking people in applying Islamic banking based on Malaysian experience in this filed. It also aimed to find the factors that affect the success of Islamic banking in Iraq and suggested applicable model that can be applied in Iraq. The research used quantitative approach through self-administrated questionnaire instrument and the use of secondary data. The target respondents were 97 Iraqi citizens living in Malaysia. The data analysis was done through SPSS version 20.0. The descriptive analysis and Pearson Correlation are used to test the hypotheses. The descriptive analysis is to find the overall Mean value score of the items. The respondents varied between agree and strongly agree on the statements that they were asked to evaluate. The highest overall Mean score value of 4.23 from the role of people of Islamic banks, followed by procedures of Islamic bank at overall Mean score value of 4.20. The other two scales were service quality and trust between Islamic banks and customers and the overall mean value score of the two scales were 4.03 and 4.02 respectively. The hypotheses were tested and accepted. The highest correlation was found to be between trust and successful establishment of Islamic bank at Pearson Correlation of .633 followed by service quality of Islamic banks at Pearson correlation of .566. Similarly, the correlation between people of Islamic bank, procedure of Islamic and the dependent variable successful establishment of Islamic bank were found positive at .562 and .524 respectively.